Institutional policy - Marambanyika, Thomas; Dube, Timothy; Musasa, Tatenda (Elsevier, 2022)
This chapter provides a detailed overview on impacts of anthropogenic activities on tropical wetlands and further elaborates on how the discrepancies between policy, legal, and institutional arrangements have affected wetlands management and conservation initiatives. Further, advancements in wetland assessment-related scientific research and key knowledge gaps as well as the associated implications on the management and policy formulation were also explored. In addition, wetland degradation and loss at the regional level, considering the interconnectedness of the river basins, were explored including challenges that occur across transboundary river basins. Spatial and temporal arrangements in terms of policies, legal setups, and differences in the composition of multiple stakeholders involved in wetland utilization and conservation are also reported. This work demonstrates that tropical wetlands are under severe stress and at risk of extinction, due to overutilization by communities. This is further worsened by the lack of clear management frameworks or policies in place and weak institutions, especially to govern unprotected wetlands. Also, considering that some of the selected Southern African countries have no comprehensive national wetland policies, the lack of a clear regional wetland policy, therefore, exposes wetlands to multiple institutional management systems that are either complementary or contradictory and conflicting with no clear overlaps. Therefore, wetland management policies should be developed and harmonized to ensure effective implementation of legislation by the participating institutions in a way that informs sustainable use at regional basin scale.